2020
DOI: 10.1071/mf18373
|View full text |Cite
|
Sign up to set email alerts
|

Global scanning of anatoxins in aquatic systems: environment and health hazards, and research needs

Abstract: Surface water contamination from the neurotoxic cyanotoxin anatoxin-a and its analogues present risks to global public health and the environment. Understanding aquatic hazards is critical for cyanobacterial blooms increasing in magnitude, frequency and duration. We examined published data to identify exceedances of guideline values (GVs) globally in various aquatic systems to understand hazards when exposure occurs. Environmental exposure distributions of surface water data (intra- and extracellular toxins) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…As observed in this experiment, higher overall N concentrations lead to higher anatoxin concentrations, with NO 3 enrichment leading to the largest increase in anatoxin production, which parallels results from other limnetic anatoxin-producing CyanoHABs [77][78][79][80][81]. Anatoxin production in Sandusky Bay and other Planktothrix-dominated bodies of water needs further examination, given the neurotoxicity and potential developmental toxicity of anatoxin [82,83] as well as its multiple deleterious environmental effects [84,85].…”
Section: Discussionsupporting
confidence: 64%
“…As observed in this experiment, higher overall N concentrations lead to higher anatoxin concentrations, with NO 3 enrichment leading to the largest increase in anatoxin production, which parallels results from other limnetic anatoxin-producing CyanoHABs [77][78][79][80][81]. Anatoxin production in Sandusky Bay and other Planktothrix-dominated bodies of water needs further examination, given the neurotoxicity and potential developmental toxicity of anatoxin [82,83] as well as its multiple deleterious environmental effects [84,85].…”
Section: Discussionsupporting
confidence: 64%
“…As observed in this experiment, higher overall N concentrations lead to higher anatoxin concentrations, with NO 3 enrichment leading to the largest increase in anatoxin production, which parallels results from other limnetic anatoxin-producing CyanoHABs [ 77 , 78 , 79 , 80 , 81 ]. Anatoxin production in Sandusky Bay and other Planktothrix -dominated bodies of water needs further examination, given the neurotoxicity and potential developmental toxicity of anatoxin [ 82 , 83 ] as well as its multiple deleterious environmental effects [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that when blooms occurred, recreational and potable source waters exceeded guidelines of 0.1, 1 and 300 mg L À1 for 79.62, 48.37 and 1.42% of the time respectively. Of the occurrences, 66% were from lacustrine ecosystems compared with reservoir, river, coastal and other systems, with almost all data from Asia-Pacific, Europe and North America (Lovin and Brooks 2020). This latter point underscores the need for more monitoring efforts in diverse systems and in developing regions.…”
Section: Cyanobacterial Toxinsmentioning
confidence: 96%